Living With Stories - Schneider, William (Utah State University, University Libraries, 2008)
In essays about communities as varied as Alaskan Native, East Indian, Palestinian, Mexican, and African American, oral historians, folklorists, and anthropologists look at how traditional and historical oral narratives live through re-tellings, gaining meaning and significance in repeated performances, from varying contexts, through cultural and historical knowing, and due to tellers' consciousness of their audiences.